2004
DOI: 10.1210/jc.2004-0446
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone and Sodium Salicylate Protect Human β-Cells against Apoptosis and Impaired Function Induced by Glucose and Interleukin-1β

Abstract: Decreased functional beta-cell mass in type 1 and type 2 diabetes is due to beta-cell apoptosis and impaired secretory function suggested to be mediated, in part, by immune- and/or high-glucose-induced production of IL-1beta acting through the nuclear factor kappaB (NFkappaB)/Fas pathway. The aim of this study was to determine whether two drugs believed to block NFkappaB activation, the thiazolidinedione (glitazone) pioglitazone and the nonsteroidal antiinflammatory drug sodium salicylate, can protect human be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(62 citation statements)
references
References 71 publications
2
58
0
2
Order By: Relevance
“…6). As expected for this population of cells sorted by FACS, most of the cells overexpressing gelsolin were ␤-cells because they also express insulin, as seen after staining with a previously characterized insulin antibody (29).…”
Section: Induction Of Apoptosis In Min6 B1 and C3 Cellssupporting
confidence: 72%
“…6). As expected for this population of cells sorted by FACS, most of the cells overexpressing gelsolin were ␤-cells because they also express insulin, as seen after staining with a previously characterized insulin antibody (29).…”
Section: Induction Of Apoptosis In Min6 B1 and C3 Cellssupporting
confidence: 72%
“…Along with improved glycaemic control and improvements in insulin resistance, beta cell 'rejuvenation' and improvements in beta cell function have been reported in several recent thiazolidinedione trials [40]. In parallel with in vitro data indicating that thiazolidinediones can protect beta cells not only from apoptosis but also from loss of function [41], the role of thiazolidinediones in directly targeting and preserving beta cell function is only now becoming clear [42].…”
Section: Discussionmentioning
confidence: 96%
“…Another mechanism involves direct actions on pancreatic beta cells [44]. Recent reports have demonstrated that thiazolidinediones directly improve beta cell function [45], ameliorate lipotoxicity [46] and prevent beta cell apoptosis [47,48]. In Wfs1 −/− A y /a mice, direct protective effects, as well as indirect effects, are likely to be exerted.…”
Section: Discussionmentioning
confidence: 99%